Online Polling System Using Extended Visual Cryptography (International Journal of Engineering and Computer Science, 2015)
Trustworthy elections are essential to democracy. The process of Election is complex and involve many components including voter registration, ballot preparation and distribution, voter authentication, vote casting, tabulation, result reporting, auditing, and validation. To make the process more secure and reliable, the standard mechanism should be deployed. Online Polling System offers many benefits including low cost & increased voter participation. Remote Voting system considers security & human factors carefully and mainly considers that they provide voters reliable and intuitive indications of the validity of the voting process. This gives rise to the concept of Secure Online polling System Using Extended Visual Cryptography, Such a technique thus would be lucrative for security. It offers many benefits including low cost, increased voter participation and consider human factor carefully.